The Importance Of Social Skill In Frances Hodgson Burnett's A Little Princess Novel (1904): A Sociological Approach - Fridayati, Linda Pratiwi, Drs. M. Thoyibi, MS., Nur Hidayat, S. Pd (2013)
The major problem of this study is how the importance of social skill is reflected in A Little Princess novel by Frances Hodgson Burnett. The objective of this study is to analyze the novel based on its structural elements and to describe the importance of social skill in the novel based on the sociological analysis. In analyzing A Little Princess, the writer uses qualitative method and sociological approach. The data sources consist of primary data and secondary data sources. The primary data source is A Little Princess novel and the secondary data sources are the other sources related to the analysis such as books of literary theory, the author's biography and the other relevant information. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusions. First, from the structural analysis of the novel, Burnett describes that children need to learn about the basic of social skill, such as greeting and asking, starting a corversation, giving opinion or response, etc. The theme of the novel also gives emphasi that people should be aware of the way of treating others and should appreciate and respect each other as well as they respect themselves. Second, based on sociological analysis, it shows that there is a close relationship between A Little Princess novel and social realities of English society in the early twentieth century.